2019
DOI: 10.17161/kjm.v10i3.8657
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Medical Student Knowledge Regarding Life-Threatening CT Images Before and After Clinical Experience

Abstract: BackgroundCurrently, no national standard exists for educating medical students regarding radiography or formal research indicating the level of improvement regarding computed tomography (CT) interpretation of medical students during clinical rotations.MethodsStudents were evaluated based on their response to twenty-two open-ended questions regarding diagnosis and treatment of eleven de-identified CT images of life-threatening injuries. The number of incorrect answers was compared with correct or partially cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…For examinations, participants were allowed to view the labeled structures in the axial, coronal, and sagittal planes and could additionally scroll through the image slices to view the progression of the structures. This modality of testing is more representative of how students will visualize CT images upon entering the clinical environment and contrasts with the more traditional use of static images for testing 17,18 . Another novel component of this project was the interdisciplinary nature by which the study was constructed as well as the learning materials provided to the students.…”
Section: Discussionmentioning
confidence: 99%
“…For examinations, participants were allowed to view the labeled structures in the axial, coronal, and sagittal planes and could additionally scroll through the image slices to view the progression of the structures. This modality of testing is more representative of how students will visualize CT images upon entering the clinical environment and contrasts with the more traditional use of static images for testing 17,18 . Another novel component of this project was the interdisciplinary nature by which the study was constructed as well as the learning materials provided to the students.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies evaluating the ability of medical students to interpret specific findings on diagnostic imaging after training have shown mixed results, with generally high accuracy for some ultrasound applications and poor accuracy for interpretation of CT. [15][16][17] In one study, nearly two-thirds of interns reported being frequently expected to make preliminary imaging study interpretations, but fewer than half felt confident in their ability to interpret basic CT images. 18 There is consensus among residency program directors that adequate radiology skills should be a part of undergraduate medical education.…”
Section: Durant Et Almentioning
confidence: 99%
“…These topics were decided based on gaps identified in the literature as well as input from instructors with experience in radiology education. [11][12][13][14] Clinicians with proficient knowledge in these specific themes were matched with the respective radiologist speakers to act as co-presenters. Prerequisites for the program included 8 hours of introductory videos covering X-ray, CT, ultrasonography, MRI, PET, contrast agents, interventional radiology, and history of radiology; these were available on-demand through the US partner educational initiative and taught by renowned radiologists from US and Canadian institutions.…”
Section: Course Development and Implementationmentioning
confidence: 99%